Analisis Stabilitas Lereng Dengan Perkuatan Geotekstil (Studi Kasus: Proyek Pembangunan Jalan Tol Cibitung - Cilincing Seksi 2 STA 6+475) - Pandu Graha Rizqullah; Yelvi Yelvi (Jurnal Ilmiah Rekayasa Sipil, 2022)
Excavation and embankment work on toll roads is a routine work due to the difference of elevation between road and ground existing. This paper This paper will discuss slope stability during earth works at Cibitung - Cilincing Toll Road Project since there are a lot of excavation and embankment works. The slope stability has to be analyzed to determine safety factor (SF). On this paper, embankment slope at STA 6+475 is reinforced by geotextile system. The safety factor is calculated using before and after reinforced by geotextile using Bishop method and PLAXIS software program. The results shows that a safety factor of 1.47 (manually) and 1.201 (PLAXIS) in static condition. For dynamic condition with coefficient of horizontal earthquake of 0,18 is obtained average of safety factor of 0.95 (manually). While the safety factor for analysis with earthquake loads using PLAXIS software program cannot be calculated, then the lateral deformation value is sought, which is 0,505 m. From this result, the slope of existing condition has to be reinforced by geotextile system since SF is less than 1.25. Reinforcement of geotextile system designed is divided into 2 zones, such as: 1.0 m and 0.5 m. Analysis of slope stability of the embankment slopes with geotextile reinforcement system is obtained a safety factor of 1.880. It means that the condition of the existing embankment slopes reachs 64%. While the value of the lateral deformationnof the embankment slope using geotextile renforcement with an earthquake load is 0,034 m, so that this value meets the allowable deformation value.